2017
DOI: 10.1371/journal.pone.0183540
|View full text |Cite
|
Sign up to set email alerts
|

Unusual cohabitation and competition between Planktothrix rubescens and Microcystis sp. (cyanobacteria) in a subtropical reservoir (Hammam Debagh) located in Algeria

Abstract: Succession in bloom-forming cyanobacteria belonging to distant functional groups in freshwater ecosystems is currently an undescribed phenomenon. However in the Hammam Debagh reservoir (Algeria), P. rubescens and Microcystis sp. co-occur and sometimes proliferate. With the aim of identifying the main factors and processes involved in this unusual cohabitation, water samples were collected monthly from February 2013 to June 2015 at the subsurface at four sampling stations and along the entire water column at on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 46 publications
4
16
0
Order By: Relevance
“…In temperate eutrophic freshwaters, Microcystis and Planktothrix may co-occur, with Planktothrix being an early colonizer and Microcystis appearing subsequently (Engelke et al, 2003;Jang et al, 2006;Pitois et al, 2014;Reichswaldt et al, 2015;Guellati et al, 2017). In a previous laboratory study, Engelke and colleagues (2003) reported an increase of MC concentrations in M. aeruginosa PCC 7820 cells in response to the presence of the non-MC-producing P. agardhii CYA 29 or its spent medium, and that this interaction led to an inhibition of P. agardhii growth.…”
Section: Introductionmentioning
confidence: 99%
“…In temperate eutrophic freshwaters, Microcystis and Planktothrix may co-occur, with Planktothrix being an early colonizer and Microcystis appearing subsequently (Engelke et al, 2003;Jang et al, 2006;Pitois et al, 2014;Reichswaldt et al, 2015;Guellati et al, 2017). In a previous laboratory study, Engelke and colleagues (2003) reported an increase of MC concentrations in M. aeruginosa PCC 7820 cells in response to the presence of the non-MC-producing P. agardhii CYA 29 or its spent medium, and that this interaction led to an inhibition of P. agardhii growth.…”
Section: Introductionmentioning
confidence: 99%
“…The dominance of this genus was also found in other Algerian reservoirs used for drinking water [Guellati et al, 2017;Nasri et al, 2007;Saoudi et al, 2015]. Microcystis blooms frequently occur in the ecosystems containing N 2 -fixing cyanobacteria belonging to the genera Aphanizomenon, Dolichospermumand Cylindrospermopsis [Wu et al, [Guellati et al, 2017]. According to [Guellati et al, 2017], these two genera were only found in a restricted number of samples, in which they have always displayed very low abundance in this water pond.…”
Section: Discussionmentioning
confidence: 71%
“…Our results show that the most dominant genus of cyanobacteria was Microcystis; this genus is present throughout the water column and during the entire year. The dominance of this genus was also found in other Algerian reservoirs used for drinking water [Guellati et al, 2017;Nasri et al, 2007;Saoudi et al, 2015]. Microcystis blooms frequently occur in the ecosystems containing N 2 -fixing cyanobacteria belonging to the genera Aphanizomenon, Dolichospermumand Cylindrospermopsis [Wu et al, [Guellati et al, 2017].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, besides the more recent discovery of populations living in Eastern Europe (Vasas et al, 2013), records of this species were documented in many Mediterranean regions, including Central and Southern Italy ( Messineo et al, 2006;Assennato et al, 2010), Sicily (Naselli-Flores and Barone, 2000), Spain (Almodóvar et al, 2004), Greece (Vareli et al, 2009) and Turkey (Akçaalan et al, 2014;Köker et al, 2017). More recently, this species has also been identified in Northern Africa (Guellati et al, 2017). The taxonomic position of this species has been widely investigated based both on phenotypic characters (Komárek and Anagnostidis, 2005) and genetic markers (D'Alelio et al, 2013;Gaget et al, 2015;Kurmayer et al, 2015;Salmaso et al, 2016;Suda et al, 2002).…”
Section: Ecological and Trophic Characterizationmentioning
confidence: 97%